Computer-assisted surgery and navigation in foot and ankle: state of the art and fields of application. Issue 7 (8th July 2021) - Kutaish, Halah; Acker, Antoine; Drittenbass, Lisca; Stern, Richard; Assal, Mathieu
Abstract : Computer-assisted orthopaedic surgery (CAOS) is a real-time navigation guidance system that supports surgeons intraoperatively. Its use is reported to increase precision and facilitate less-invasive surgery. Advanced intraoperative imaging helps confirm that the initial aim of surgery has been achieved and allows for immediate adjustment when required. The complex anatomy of the foot and ankle, and the associated wide range of challenging procedures should benefit from the use of CAOS; however, reports on the topic are scarce. This article explores the fields of applications of real-time navigation and CAOS in foot and ankle surgery. Cite this article: EFORT Open Rev 2021;6:531-538. DOI: 10.1302/2058-5241.6.200024